2007
DOI: 10.2110/sedred.2007.4.4
|View full text |Cite
|
Sign up to set email alerts
|

Late Holocene barrier island collapse: Outer Banks, North Carolina, USA

Abstract: We document here the threat of large scale destruction (collapse) of barrier islands based on the study of many cores taken along the Outer Banks and in Pamlico Sound, North Carolina.Around 1,100 cal yr BP, probably as the result of hurricane activity, portions of the southern Outer Banks must have collapsed to allow normal salinity waters to bathe southern Pamlico Sound for several hundred years. Such collapse could occur again during our current regime of global warming, rising sea level and increased tropic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
60
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(65 citation statements)
references
References 8 publications
5
60
0
Order By: Relevance
“…4 cal kyr B.P. This coincides with a proposed period of barrier island collapse (Culver et al, 2007) when Pamlico Sound had normal marine salinity, probably due to a lack of coastal barriers. If coastal barriers were absent, the timing suggests that the former cape may have existed for ~5 k.y.…”
Section: Evidence Of An Abandoned Capesupporting
confidence: 67%
“…4 cal kyr B.P. This coincides with a proposed period of barrier island collapse (Culver et al, 2007) when Pamlico Sound had normal marine salinity, probably due to a lack of coastal barriers. If coastal barriers were absent, the timing suggests that the former cape may have existed for ~5 k.y.…”
Section: Evidence Of An Abandoned Capesupporting
confidence: 67%
“…11D). Culver et al (2007) suggest that at this same time, portions of the southern Outer Banks (north of Bogue Banks) "collapsed", creating a segmented barrier system. It is postulated that this was the result of increased hurricane activity due to warmer temperatures during the medieval climate anomaly (Cronin et al, 2003;Culver et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Culver et al (2007) suggest that at this same time, portions of the southern Outer Banks (north of Bogue Banks) "collapsed", creating a segmented barrier system. It is postulated that this was the result of increased hurricane activity due to warmer temperatures during the medieval climate anomaly (Cronin et al, 2003;Culver et al, 2007). Mann et al (2009) corroborate this assertion by comparing the sedimentary record of land-falling hurricanes to statistical-model estimates of cyclone activity over approximately the last 1500 yr that shows a period of high cyclone activity in the Atlantic during the medieval climate anomaly,~1100-900 cal yr BP.…”
Section: Discussionmentioning
confidence: 99%
“…4b) are predominately sand, and could have provided a sufficient quantity of sediments for the ultimate development of shoals and barrier islands. Culver et al (2007) found that the position of the North Carolina Outer Banks barrier islands is related to a former topographic high. They propose that the initial formation of the Outer Banks occurred on the crest of a Pleistocene interstream divide as rising post-glacial sea level flooded the incised fluvial topography.…”
Section: Discussionmentioning
confidence: 97%